2021
DOI: 10.1097/cm9.0000000000001552
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol promotes chondrocyte autophagy by regulating mTOR expression

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In the mTORC1, the highly conserved serine/threonine kinase mTOR is the central catalytic subunit of the multiprotein complex and may phosphorylate multiple autophagy proteins, which results in a blockade of autophagy-initiating kinase ULK1 and functions as a negative autophagy mediator ( 78 ). Transcriptomics data and network pharmacology analysis predicted that mTOR is the direct therapeutic target of celastrol against osteoarthritis ( 79 ), and a subsequent study validated that the promotion of chondrocyte autophagy by celastrol occurs as a result of the reduction in mTOR levels ( 39 ). In addition, numerous signaling pathways converging at mTOR involve celastrol-mediated autophagy.…”
Section: Mechanisms Underlying Autophagy Modulation By Celastrolmentioning
confidence: 97%
See 2 more Smart Citations
“…In the mTORC1, the highly conserved serine/threonine kinase mTOR is the central catalytic subunit of the multiprotein complex and may phosphorylate multiple autophagy proteins, which results in a blockade of autophagy-initiating kinase ULK1 and functions as a negative autophagy mediator ( 78 ). Transcriptomics data and network pharmacology analysis predicted that mTOR is the direct therapeutic target of celastrol against osteoarthritis ( 79 ), and a subsequent study validated that the promotion of chondrocyte autophagy by celastrol occurs as a result of the reduction in mTOR levels ( 39 ). In addition, numerous signaling pathways converging at mTOR involve celastrol-mediated autophagy.…”
Section: Mechanisms Underlying Autophagy Modulation By Celastrolmentioning
confidence: 97%
“…Extensive experimentation has indicated that autophagy modulation may be an important mechanism underlying the anti-tumor therapeutic effect of celastrol (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Celastrol also alleviates inflammatory reactions and restrains the immune response through autophagic pathways (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Furthermore, autophagy has a role when celastrol exerts neuroprotective, anti-atherosclerosis, anti-pulmonary fibrosis and anti-macular degeneration effects (41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Autophagy Regulation By Celastrolmentioning
confidence: 99%
See 1 more Smart Citation
“…Many small molecule compounds and natural plant components play protective roles in OA by activating autophagy, such as isoimperatorin, delphinidin, celastrol, curcumin and astragaloside IV ( Liu, Meng, Jing, & Zhou, 2017 ; Ouyang, Jiang, Fang, Cui, & Cai, 2017 ; Lee et al, 2020 ; Xiao et al, 2020 ; Dai et al, 2021 ). Baicalin protects chondrocytes against the degradation of ECM through activating autophagy via miR-766-3p/AIFM1 axis ( Li, Cheng, & Liu, 2020 ).…”
Section: Drugs Targeting Autophagy For Osteoarthritis Treatmentmentioning
confidence: 99%